Anchor peptides: A green and versatile method for polypropylene functionalization. (5th May 2017) - Rübsam, Kristin; Stomps, Benjamin; Böker, Alexander; Jakob, Felix; Schwaneberg, Ulrich
Abstract: Polypropylene is one of the widest spread commodity polymers in plastic industry with an estimated global consumption of 62.4 million tons in 2020. Surface modification of polypropylene is required for its application as textile fibers, packaging material or filtration membranes. Modification of polypropylene is challenging due to absent functional surface groups. An anchor-peptide-based toolbox for green and versatile polypropylene functionalization was developed. Fusion proteins composed of enhanced green fluorescent protein (EGFP) and anchor peptides (e.g. cecropin A or LCI) were designed and applied to polypropylene surfaces. Resulting protein coatings of EGFP-LCI were characterized by fluorescence and scanning force microscopy. The fusion protein EGFP-LCI formed densely packed monolayers of 4.1 ± 0.2 nm thickness. A microtiter plate-based fluorescence assay was developed to analyze the coating in presence of surfactants. Washing of EGFP-LCI coated polypropylene with 10 mM non-ionic surfactant (Triton X-100) did not detach the protein film, whereas EGFP was removed completely. Anchor peptides promote binding to polypropylene by simple dip-coating at room temperature in water. The high coating density (0.8 pmol/cm 2 ) as well as the number and diversity of provided functional groups offer a viable alternative to conventional modification strategies of functionalizing polypropylene. LCI's role as broadly applicable adhesion promoter was demonstrated by equipping polypropylene with the fluorescent dye ThioGlo-1 via the anchor peptide LCI. Graphical abstract: Highlights: Utilization of antimicrobial peptides as material binding peptides. Polypropylene functionalization by simple dip coating with anchor peptides. Peptide LCI forms stable monolayer on polypropylene at room temperature in water. High coating density and further functionalization possible via coupling reactions.